Magnetic composition
By using magnetic powder with a specific particle size distribution in a magnetic composition, the trade-off between relative magnetic permeability and magnetic loss is resolved, resulting in improved performance of magnetic sheets, circuit boards, and inductor boards with reduced loss and increased permeability.
Patent Information
- Application Number
- JP2020060278
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-30
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-03-30
AI Technical Summary
There is a trade-off relationship between relative magnetic permeability and magnetic loss in magnetic layers, making it difficult to improve both simultaneously in inductor components.
Incorporating magnetic powder with a predetermined particle size distribution, specifically 10% particle size (D10) of 1.7μm to 2.6μm, 50% particle size (D50) of 3.6μm to 12.0μm, and 90% particle size (D90) of 25.0μm to 51.0μm, into a magnetic composition, which includes a binder resin and optional components like a curing accelerator and dispersant, to form a cured product with improved relative magnetic permeability and reduced magnetic loss.
The magnetic composition achieves a cured product with enhanced relative magnetic permeability and reduced magnetic loss, suitable for use in magnetic sheets, circuit boards, and inductor boards, providing high performance in inductor elements and through-hole filling applications.
Smart Images

Figure 0007599833000003 
Figure 0007599833000004 
Figure 0007599833000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic composition, and a magnetic sheet, a circuit board, and an inductor board obtained by using the magnetic composition. [Background technology]
[0002] Circuit boards such as printed wiring boards may be provided with a magnetic layer containing magnetic powder for inductor components, etc. For example, Patent Document 1 describes a silicon oxide-coated soft magnetic powder in which soft magnetic powder is surface-treated with silicon oxide as the magnetic powder contained in the magnetic layer in order to suppress the reduction of magnetic loss. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-143241 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, in order to further improve the performance of inductor components, there is a demand for a technology capable of forming a magnetic layer with low magnetic loss. For this reason, the present inventors have studied the relative permeability and magnetic loss of the magnetic layer, and have found that an attempt to improve the relative permeability increases the magnetic loss, and an attempt to reduce the magnetic loss decreases the relative permeability, and thus there is a trade-off relationship between increasing the relative permeability and reducing the magnetic loss.
[0005] The present invention has been made in consideration of the above circumstances, and has an object to provide a magnetic composition that can give a cured product with improved relative permeability and reduced magnetic loss, and a magnetic sheet, a circuit board, and an inductor board obtained using the magnetic composition. [Means for solving the problem]
[0006] As a result of extensive research, the inventors discovered that the trade-off between relative permeability and magnetic loss can be eliminated by incorporating a magnetic powder having a predetermined particle size distribution into a magnetic composition, and thus completed the present invention.
[0007] That is, the present invention includes the following. [1] (A) Magnetic powder, and (B) a binder resin; (A) 10% particle size in the particle size distribution of the component (D 10 ) is 1.7μm or more and 2.6μm or less, 50% particle size (D 50 ) is 3.6μm or more and 12.0μm or less, and 90% particle size (D 90 ) is 25.0 μm or more and 51.0 μm or less. [2] The magnetic composition according to [1], wherein component (A) is a soft magnetic powder. [3] The magnetic composition according to [1] or [2], wherein component (A) is either a nanocrystalline magnetic material or an amorphous magnetic material. [4] The magnetic composition according to any one of [1] to [3], wherein component (A) contains an iron alloy metal powder. [5] The magnetic composition according to any one of [1] to [4], wherein the component (A) is either an Fe-based nanocrystalline magnetic material or an Fe-based amorphous magnetic material. [6] The magnetic composition according to any one of [1] to [5], which is for forming an inductor element. [7] The magnetic composition according to any one of [1] to [6], which is in a paste form. [8] The magnetic composition according to any one of [1] to [7], which is for filling a through-hole. [9] A magnetic sheet comprising a support and a magnetic composition layer formed on the support from the magnetic composition according to any one of [1] to [8].
[10] A circuit board comprising a magnetic layer which is a cured product of the magnetic composition according to any one of [1] to [8].
[11] A circuit board comprising: a substrate having a through-hole; and a cured product of the magnetic composition according to any one of [1] to [8] filled in the through-hole.
[12] An inductor substrate comprising the circuit substrate according to
[10] or
[11] . Effect of the Invention
[0008] According to the present invention, it is possible to provide a magnetic composition which can give a cured product having improved relative magnetic permeability and reduced magnetic loss, as well as a magnetic sheet, a circuit board, and an inductor board obtained using the magnetic composition. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of a core substrate as an example of a method for manufacturing a circuit board according to a first embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a core substrate in which a through hole is formed, as an example of the method for manufacturing the circuit board according to the first embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a state of a core board in which a plating layer has been formed in a through-hole as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a core board in which a magnetic composition has been filled in through-holes, as an example of the method for producing the circuit board of the first embodiment. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing the state of a core substrate in which the filled magnetic composition has been thermally cured, as an example of the method for producing the circuit board of the first embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view showing the state of the core substrate after polishing the cured product as an example of the method for producing the circuit board according to the first embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view showing a state of a core substrate with a conductor layer formed on a polished surface thereof as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 8] FIG. 8 is a schematic cross-sectional view showing the state of a core substrate on which a pattern conductor layer is formed as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 9]FIG. 9 is a schematic cross-sectional view for illustrating step (A) included in an example of the method for producing the circuit board according to the second embodiment. [Figure 10] FIG. 10 is a schematic cross-sectional view for illustrating step (A) included in an example of the method for producing the circuit board according to the second embodiment. [Figure 11] FIG. 11 is a schematic cross-sectional view for explaining step (B) included in the example of the method for manufacturing the circuit board according to the second embodiment. [Figure 12] FIG. 12 is a schematic cross-sectional view for explaining step (D) included in the example of the method for producing the circuit board according to the second embodiment. [Figure 13] FIG. 13 is a schematic plan view of an inductor component including a circuit board obtained by the circuit board manufacturing method according to the second embodiment, as an example, viewed from one side in the thickness direction. [Figure 14] FIG. 14 is a schematic diagram showing a cut end surface of an inductor component including a circuit board obtained by the manufacturing method for a circuit board of the second embodiment, cut at the position indicated by the dashed line II-II in FIG. 13 as an example. [Figure 15] FIG. 15 is a schematic plan view illustrating the configuration of a first conductor layer in an inductor component including a circuit board obtained by the method for manufacturing a circuit board according to the second embodiment, as an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that each drawing merely shows the shape, size, and arrangement of components in a schematic manner to the extent that the invention can be understood. The present invention is not limited to the following embodiment, and each component can be modified as appropriate. Furthermore, the configuration according to the embodiment of the present invention is not necessarily manufactured or used according to the arrangement of the illustrated example.
[0011] [Magnetic composition] The magnetic composition of the present invention contains (A) a magnetic powder and (B) a binder resin, and has a 10% particle size (D 10) is 1.7μm or more and 2.6μm or less, 50% particle size (D 50 ) is 3.6μm or more and 12.0μm or less, and 90% particle size (D 90 ) is 25.0 μm or more and 51.0 μm or less. In the present invention, by incorporating a magnetic powder having a predetermined particle size distribution in the magnetic composition, it is possible to achieve both an improvement in the relative magnetic permeability and a reduction in magnetic loss in the cured product of this magnetic composition.
[0012] The magnetic composition may further contain, as necessary, (C) a hardening accelerator, (D) a dispersant, and (E) other additives. Each component contained in the magnetic composition of the present invention will be described in detail below.
[0013] <(A) Magnetic powder> The magnetic composition contains magnetic powder as component (A), and has a 10% particle size (D 10 ) is 1.7μm or more and 2.6μm or less, 50% particle size (D 50 ) is 3.6μm or more and 12.0μm or less, and 90% particle size (D 90 ) has a particle size distribution of 25.0 μm or more and 51.0 μm or less. The above particle size distribution represents the particle size distribution of the entire magnetic powder (A) contained in the magnetic composition. By including component (A) in the magnetic composition, it is possible to simultaneously improve the relative magnetic permeability of the cured product and reduce magnetic loss.
[0014] (A) The particle size distribution of magnetic powder can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of magnetic powder is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the 10% particle size (D 10 ), 50% particle size (D 50 ), and 90% particle size (D 90 ) can be measured. A measurement sample can be preferably prepared by dispersing magnetic powder in pure water using ultrasonic waves. As a laser diffraction scattering type particle size distribution measuring device, the "MT3000II" manufactured by Microtrackbell, the "LA-960" manufactured by Horiba, Ltd., the "SALD-2200" manufactured by Shimadzu Corporation, etc. can be used.
[0015] 10% particle size in particle size distribution (D 10 50% particle size (D ) refers to the particle size at which the cumulative volume from the smallest particle size in the particle size distribution is 10% as a result of measuring the particle size distribution by the above method. 50 ) refers to the particle size at which the cumulative volume from the smallest particle size in the particle size distribution is 50% as measured by the above method. Also, the 90% particle size (D 90 ) refers to the particle size at which the cumulative volume from the smallest particle size in the particle size distribution is 90% as a result of measuring the particle size distribution by the above method. Here, the average particle size of the (A) magnetic powder is the 50% particle size (D 50 ) particle size. Hereinafter, 10% particle size (D 10 ) to D 10 , 50% particle size (D 50 ) to D 50 , and 90% particle size (D 90 ) to D 90 This is what happens.
[0016] D in particle size distribution 10 From the viewpoint of enabling both improvement of the relative magnetic permeability of the cured product of the magnetic composition and reduction of magnetic loss, the thickness is 1.7 μm or more, preferably 1.8 μm or more, and more preferably 1.9 μm or more. The upper limit is 2.6 μm or less, preferably 2.5 μm or less, and more preferably 2.4 μm or less.
[0017] D in particle size distribution 50 From the viewpoint of enabling both improvement of the relative magnetic permeability of the cured product of the magnetic composition and reduction of magnetic loss, the thickness is 3.6 μm or more, preferably 4.0 μm or more, and more preferably 5.0 μm or more. The upper limit is 12.0 μm or less, preferably 11.0 μm or less, and more preferably 10.0 μm or less.
[0018] D in particle size distribution 90From the viewpoint of enabling both improvement of the relative magnetic permeability of the cured product of the magnetic composition and reduction of magnetic loss, the thickness is 25.0 μm or more, preferably 26.0 μm or more, and more preferably 27.0 μm or more. The upper limit is 51.0 μm or less, preferably 50.0 μm or less, and more preferably 49.0 μm or less.
[0019] D 50 -D 10 From the viewpoint of obtaining the effects of the present invention remarkably, the thickness is preferably 1.0 μm or more, more preferably 1.1 μm or more, and even more preferably 1.2 μm or more. The upper limit is preferably 10.3 μm or less, more preferably 10.2 μm or less, and even more preferably 10.1 μm or less.
[0020] D 90 -D 10 From the viewpoint of obtaining the effects of the present invention significantly, the thickness is preferably 22.4 μm or more, more preferably 22.5 μm or more, and even more preferably 22.6 μm or more. The upper limit is preferably 49.3 μm or less, more preferably 49.2 μm or less, and even more preferably 49.1 μm or less.
[0021] D 90 -D 50 From the viewpoint of obtaining the effects of the present invention remarkably, the thickness is preferably 13 μm or more, more preferably 14 μm or more, and even more preferably 15 μm or more. The upper limit is preferably 47.4 μm or less, more preferably 47.0 μm or less, and even more preferably 46.0 μm or less.
[0022] D 90 / D 50 From the viewpoint of obtaining the effects of the present invention remarkably, the lower limit is preferably 14.17 or less, more preferably 12.75 or less, and even more preferably 10.20 or less. The lower limit is preferably 2.08 or more, more preferably 2.27 or more, and even more preferably 2.50 or more.
[0023] D 90 / D 10From the viewpoint of obtaining the effects of the present invention remarkably, the lower limit is preferably 30.0 or less, more preferably 28.3 or less, and even more preferably 26.8 or less. The lower limit is preferably 9.62 or more, more preferably 10 or more, and even more preferably 10.4 or more.
[0024] D 50 / D 10 From the viewpoint of obtaining the effects of the present invention remarkably, the lower limit is preferably 7.06 or less, more preferably 6.67 or less, and even more preferably 6.32 or less. The lower limit is preferably 1.38 or more, more preferably 1.44 or more, and even more preferably 1.89 or more.
[0025] The (A) magnetic powder may be either a soft magnetic powder or a hard magnetic powder, but from the viewpoint of suppressing uneven distribution of the magnetic powder, a soft magnetic powder is preferable.
[0026] The (A) magnetic powder is preferably either a nanocrystalline magnetic material or an amorphous magnetic material from the viewpoint of enabling both improvement of the relative magnetic permeability of the cured product of the magnetic composition and reduction of the magnetic loss, and is more preferably a nanocrystalline magnetic material from the viewpoint of enabling reduction of the magnetic loss by reducing the magnetic anisotropy of the crystals. In this specification, the nanocrystalline magnetic material refers to a magnetic material containing crystal grains, the grain size of the magnetic powder including 100 nm or less, preferably the maximum grain size of the crystal grains being 100 nm or less. Usually, one particle of the (A) magnetic powder contains a plurality of crystal grains, and the particle can be polycrystalline. The size of the crystal grains can be observed, for example, by a TEM (transmission electron microscope). Since the nanocrystalline magnetic material contains crystal grains, it can usually show a peak showing crystallinity in the X-ray diffraction pattern. In addition, the amorphous magnetic material refers to a non-crystalline magnetic material that does not show a specific peak showing crystallinity in the X-ray diffraction pattern. Normally, the X-ray diffraction pattern of an amorphous magnetic material shows a broad pattern without any peaks indicating crystallinity. (A) By using either a nanocrystalline magnetic material or an amorphous magnetic material as the magnetic powder, the magnetic flux density increases, and as a result, it is believed that it is possible to effectively achieve both an improvement in relative permeability and a reduction in magnetic loss.
[0027] (A) Examples of the magnetic powder include iron alloy metal powders (Fe-based metal powders) such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Cr-Si alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, and Fe-Ni-Co alloy powder.
[0028] Among them, the (A) magnetic powder is preferably an iron alloy metal powder from the viewpoint of obtaining the effect of the present invention remarkably. The iron alloy metal powder preferably contains at least one selected from Fe, Si, Cr, Al, Ni, and Co, and more preferably contains an iron alloy metal powder containing Fe, Si, and Cr. In addition, it is more preferable that the magnetic powder is either a nanocrystalline magnetic material or an amorphous magnetic material containing at least one selected from Fe, Si, Cr, Al, Ni, and Co, and it is even more preferable that the magnetic powder is either a nanocrystalline magnetic material or an amorphous magnetic material containing Fe, Si, and Cr, and it is preferably either an Fe-based nanocrystalline magnetic material or an Fe-based amorphous magnetic material, and it is more preferable that the magnetic powder is an Fe-based nanocrystalline magnetic material. Here, the Fe-based means that the magnetic powder contains Fe atoms.
[0029] The magnetic powder (A) can be adjusted to a desired particle size distribution, for example, by classification. The above particle size distribution represents the particle size distribution of the entire component (A) contained in the magnetic composition. Therefore, the component (A) formed by mixing two or more types of magnetic powders may be adjusted to have a desired particle size distribution, for example, by mixing multiple magnetic powders that do not have the desired particle size distribution, so that the entire component (A) has the desired particle size distribution.
[0030] (A) The magnetic powder may be used alone or in combination of two or more kinds, but from the viewpoint of obtaining the effect of the present invention remarkably, it is preferable to use two or more kinds of magnetic powders in combination, and it is more preferable to use two or more kinds of magnetic powders with different average particle sizes in combination. In one embodiment, when two kinds of magnetic powders with different average particle sizes are used in combination, the average particle size of one magnetic powder is preferably 0.01 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. It is also preferably less than 10 μm, more preferably 9 μm or less, and even more preferably 8 μm or less. The average particle size of the other magnetic powder is preferably 10 μm or more, more preferably 13 μm or more, and even more preferably 15 μm or more. It is also preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 23 μm or less.
[0031] In the case of using two or more kinds of magnetic powders with different average particle sizes in combination, where the average particle size of one magnetic powder is a1 and the average particle size of the other magnetic powder is a2, a1 / a2 is preferably 1 or more, more preferably 3 or more, and even more preferably 5 or more, and is preferably 15 or less, more preferably 10 or less, and even more preferably 8 or less, with the proviso that a1>a2. By adjusting a1 / a2 to be within this range, the effects of the present invention can be obtained significantly.
[0032] As the (A) magnetic powder, commercially available products can be used, and two or more types may be used in combination. Specific examples of commercially available magnetic powders that can be used include "KUAMET NC1" and "ATFINE NC1" (nanocrystalline magnetic materials) manufactured by Epson Atmix, and "KUAMET 6B2" and "AW02-08PF3F" (amorphous magnetic materials) manufactured by Epson Atmix.
[0033] (A) The magnetic powder is preferably spherical. The value (aspect ratio) obtained by dividing the length of the long axis of the magnetic powder by the length of the short axis is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1.2 or less, and is preferably more than 1, more preferably 1.05 or more. In general, it is easier to improve the relative magnetic permeability when the magnetic powder is flat rather than spherical, but in the present invention, it is preferable to use spherical magnetic powder from the viewpoint of reducing magnetic loss and obtaining a magnetic composition having a preferable viscosity.
[0034] (A) The specific surface area of the magnetic powder is preferably 0.05 m from the viewpoint of improving the relative magnetic permeability. 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more. Also, preferably 15m 2 / g or less, more preferably 12m 2 / g or less, more preferably 10m 2 / g or less. (A) The specific surface area of the magnetic powder can be measured by the BET method.
[0035] From the viewpoint of improving the relative magnetic permeability and reducing magnetic loss, the content (volume %) of the (A) magnetic powder is preferably 10% by volume or more, more preferably 20% by volume or more, and even more preferably 30% by volume or more, when the non-volatile components in the magnetic composition are taken as 100% by volume, and is preferably 95% by volume or less, more preferably 90% by volume or less, and even more preferably 80% by volume or less.
[0036] From the viewpoint of improving the relative magnetic permeability and reducing magnetic loss, the content (mass%) of the (A) magnetic powder is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on 100 mass% of the non-volatile components in the magnetic composition, and is preferably 99.5 mass% or less, more preferably 99 mass% or less, and even more preferably 98 mass% or less. In the present invention, the content of each component in the magnetic composition is a value when the non-volatile components in the magnetic composition are taken as 100 mass %, unless otherwise specified.
[0037] <(B) Binder resin> The magnetic composition contains a binder resin (B) as the component (B). Examples of the binder resin (B) include thermosetting resins such as epoxy resins, phenolic resins, naphthol resins, benzoxazine resins, active ester resins, cyanate ester resins, carbodiimide resins, amine resins, and acid anhydride resins; and thermoplastic resins such as phenoxy resins, acrylic resins, polyvinyl acetal resins, butyral resins, polyimide resins, polyamideimide resins, polyethersulfone resins, and polysulfone resins. The component (B) may contain a thermosetting resin, may contain a thermoplastic resin, or may contain both in combination. The binder resin (B) preferably contains a thermosetting resin used when forming an insulating layer of a wiring board, and among them, an epoxy resin is preferable. The binder resin (B) may be used alone or in combination of two or more. Each resin will be described below.
[0038] Here, components that can react with epoxy resins to harden the magnetic composition, such as phenol-based resins, naphthol-based resins, benzoxazine-based resins, active ester-based resins, cyanate ester-based resins, carbodiimide-based resins, amine-based resins, and acid anhydride-based resins, are sometimes collectively referred to as "curing agents."
[0039] -Thermosetting resin- Examples of epoxy resins as thermosetting resins include glycerol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthol novolac type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, and other epoxy resins having a condensed ring structure, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane dimethanol type epoxy resins, trimethylol type epoxy resins, and tetraphenylethane type epoxy resins. The epoxy resins may be used alone or in combination of two or more. The epoxy resin is preferably at least one selected from bisphenol A type epoxy resins and bisphenol F type epoxy resins.
[0040] The epoxy resin preferably contains an epoxy resin having two or more epoxy groups in one molecule. The epoxy resin preferably has an aromatic structure, and when two or more epoxy resins are used, it is more preferable that at least one of them has an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles. The ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of the non-volatile components of the epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0041] Epoxy resins include epoxy resins that are liquid at a temperature of 25° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 25° C. (hereinafter sometimes referred to as "solid epoxy resins"). When an epoxy resin is contained as component (B), the epoxy resin may contain only a liquid epoxy resin, may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin. Of these, it is preferable that the epoxy resin contains only a liquid epoxy resin from the viewpoint of reducing the viscosity of the resin composition.
[0042] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred, and glycirol type epoxy resin, bisphenol A type epoxy resin, and bisphenol F type epoxy resin are more preferred. Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL" (bisphenol A type epoxy resin), "jER807" (bisphenol F type epoxy resin), and "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin (ADEKA glycirol)) and "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation. Examples of such epoxy resins include "EP-4088S" (dicyclopentadiene type epoxy resin); "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase Chemtex Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) and "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane) manufactured by Nippon Steel Chemical & Material Co., Ltd. These may be used alone or in combination of two or more types.
[0043] As the solid epoxy resin, naphthalene-type tetrafunctional epoxy resin, cresol novolac-type epoxy resin, dicyclopentadiene-type epoxy resin, trisphenol-type epoxy resin, naphthol-type epoxy resin, biphenyl-type epoxy resin, naphthylene ether-type epoxy resin, anthracene-type epoxy resin, bisphenol A-type epoxy resin, and tetraphenylethane-type epoxy resin are preferred, and naphthalene-type tetrafunctional epoxy resin, naphthol-type epoxy resin, and biphenyl-type epoxy resin are more preferred. Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200" (dicyclopentadiene type epoxy resin), "HP-7200HH", "HP-7200H", "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000L" (naphthol novolac type epoxy resin), manufactured by DIC Corporation. 00, "NC3000L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bixylenol type epoxy resin), "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "PG-100", "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), "jER1031S" (tetraphenylethane type epoxy resin), etc. may be mentioned. These may be used alone or in combination of two or more types.
[0044] When a liquid epoxy resin and a solid epoxy resin are used in combination as the component (B), the ratio by mass (liquid epoxy resin:solid epoxy resin) is preferably 1:0.1 to 1:4, more preferably 1:0.3 to 1:3.5, and even more preferably 1:0.6 to 1:3.
[0045] The epoxy equivalent of the epoxy resin as component (B) is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, the crosslink density of the cured product is sufficient, and a magnetic layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236 and is the mass of a resin containing one equivalent of epoxy groups.
[0046] The weight average molecular weight of the epoxy resin as component (B) is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0047] As the active ester resin, a resin having one or more active ester groups in one molecule can be used. Among them, as the active ester resin, a resin having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferable. The active ester resin is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferable, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferable.
[0048] Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.
[0049] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0050] Preferred specific examples of the active ester resin include active ester resins containing a dicyclopentadiene-type diphenol structure, active ester resins containing a naphthalene structure, active ester resins containing an acetylated product of phenol novolac, and active ester resins containing a benzoylated product of phenol novolac. Among them, active ester resins containing a naphthalene structure and active ester resins containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.
[0051] Commercially available active ester resins include active ester resins containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation); active ester resins containing a naphthalene structure, such as "EXB9416-70BK" and "EXB-8150-65T" (manufactured by DIC Corporation); and active ester resins containing an acetylated product of phenol novolac. Examples of resins include "DC808" (manufactured by Mitsubishi Chemical Corporation); active ester resins containing benzoyl phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation); active ester resins which are acetylated phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation); and active ester resins which are benzoyl phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation).
[0052] As the phenolic resin and naphtholic resin, those having a novolac structure are preferred from the viewpoint of heat resistance and water resistance, and from the viewpoint of adhesion to the conductor layer, nitrogen-containing phenolic curing agents are preferred, and triazine skeleton-containing phenolic resins are more preferred.
[0053] Specific examples of phenol-based resins and naphthol-based resins include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemical Industry Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", and "EXB-9500" manufactured by DIC Corporation.
[0054] Specific examples of benzoxazine resins include "JBZ-OD100" (benzoxazine ring equivalent: 218), "JBZ-OP100D" (benzoxazine ring equivalent: 218), and "ODA-BOZ" (benzoxazine ring equivalent: 218) manufactured by JFE Chemical Corporation; "Pd" (benzoxazine ring equivalent: 217) and "Fa" (benzoxazine ring equivalent: 217) manufactured by Shikoku Chemical Industry Co., Ltd.; and "HFB2006M" (benzoxazine ring equivalent: 432) manufactured by Showa Polymer Co., Ltd.
[0055] Examples of cyanate ester resins include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester resins include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.
[0056] Specific examples of carbodiimide resins include Carbodilite (registered trademark) V-03 (carbodiimide group equivalent: 216, V-05 (carbodiimide group equivalent: 262), V-07 (carbodiimide group equivalent: 200); V-09 (carbodiimide group equivalent: 200), all manufactured by Nisshinbo Chemical Inc.; and Stavaxol (registered trademark) P (carbodiimide group equivalent: 302), all manufactured by Rhein Chemie.
[0057] Examples of the amine-based resin include resins having one or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, and aromatic amines. Among these, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based resin is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine-based curing agent include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)- ... Examples of suitable amine resins include bis(4-aminophenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, and bis(4-(3-aminophenoxy)phenyl)sulfone. Commercially available amine resins may be used, such as "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0058] Examples of the acid anhydride resin include resins having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride resin include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid.
[0059] When the epoxy resin and the curing agent are contained as the component (B), the ratio of the amount of the epoxy resin to the amount of all the curing agents is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.5 to 1:3, and even more preferably 1:1 to 1:2, in terms of the ratio of [total number of epoxy groups in the epoxy resin]:[total number of reactive groups in the curing agent]. Here, the "number of epoxy groups in the epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the magnetic composition by the epoxy equivalent. In addition, the "number of active groups in the curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the curing agent present in the magnetic composition by the active group equivalent.
[0060] -Thermoplastic resin- The polystyrene-equivalent weight average molecular weight of the thermoplastic resin is preferably 30,000 or more, more preferably 50,000 or more, and even more preferably 100,000 or more. Also, it is preferably 1,000,000 or less, more preferably 750,000 or less, and even more preferably 500,000 or less. The polystyrene-equivalent weight average molecular weight of the thermoplastic resin is measured by gel permeation chromatography (GPC). Specifically, the polystyrene-equivalent weight average molecular weight of the thermoplastic resin is measured at a column temperature of 40° C. using Shimadzu Corporation's "LC-9A / RID-6A" as a measuring device, Showa Denko Corporation's "Shodex K-800P / K-804L / K-804L" as a column, and chloroform or the like as a mobile phase, and can be calculated using a calibration curve of standard polystyrene.
[0061] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin may be used alone or in combination of two or more kinds. Specific examples of phenoxy resins include "1256" and "4250" (both of which are phenoxy resins containing a bisphenol A skeleton), "YX8100" (phenoxy resin containing a bisphenol S skeleton), and "YX6954" (phenoxy resin containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation. Other examples include "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd., and "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0062] As the acrylic resin, from the viewpoint of further reducing the coefficient of thermal expansion and the modulus of elasticity, a functional group-containing acrylic resin is preferable, and an epoxy group-containing acrylic resin having a glass transition temperature of 25° C. or lower is more preferable.
[0063] The number average molecular weight (Mn) of the functional group-containing acrylic resin is preferably 10,000 to 1,000,000, and more preferably 30,000 to 900,000.
[0064] The functional group equivalent of the functional group-containing acrylic resin is preferably 1,000 to 50,000, and more preferably 2,500 to 30,000.
[0065] The epoxy group-containing acrylic resin having a glass transition temperature of 25° C. or less is preferably an epoxy group-containing acrylic ester copolymer resin having a glass transition temperature of 25° C. or less, and specific examples thereof include "SG-80H" manufactured by Nagase ChemteX Corporation (epoxy group-containing acrylic ester copolymer resin (number average molecular weight Mn: 350,000 g / mol, epoxy value 0.07 eq / kg, glass transition temperature 11° C.)) and "SG-P3" manufactured by Nagase ChemteX Corporation (epoxy group-containing acrylic ester copolymer resin (number average molecular weight Mn: 850,000 g / mol, epoxy value 0.21 eq / kg, glass transition temperature 12° C.)).
[0066] Specific examples of polyvinyl acetal resins and butyral resins include Denka Butyral "4000-2", "5000-A", "6000-C", and "6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd., S-LEC BH series, BX series, KS series such as "KS-1", BL series such as "BL-1", and BM series, manufactured by Sekisui Chemical Co., Ltd.
[0067] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (polyimides described in JP-A-2002-12667 and JP-A-2000-319386, etc.).
[0068] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0069] A specific example of a polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. A specific example of a polyphenylene ether resin is "OPE-2St 1200", an oligophenylene ether-styrene resin having a vinyl group manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0070] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0071] Among them, the thermoplastic resin is preferably one or more resins selected from phenoxy resins, polyvinyl acetal resins, butyral resins, and acrylic resins, each having a weight average molecular weight of 30,000 or more and 1,000,000 or less.
[0072] From the viewpoint of obtaining a magnetic layer exhibiting good mechanical strength and insulation reliability, the content of the (B) binder resin is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 1% by mass or more, when the non-volatile components in the magnetic composition are taken as 100% by mass. The upper limit is not particularly limited as long as the effects of the present invention are achieved, but is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0073] The (B) binder resin preferably contains an epoxy resin, and more preferably contains a liquid epoxy resin. The liquid epoxy resin is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more, based on 100% by mass of the (A) component. The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0074] <(C) Curing accelerator> The magnetic composition may further contain (C) a curing accelerator as an optional component.
[0075] Examples of the curing accelerator include amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. From the viewpoint of reducing the viscosity of the magnetic composition, the curing accelerator is preferably an amine-based curing accelerator or an imidazole-based curing accelerator, and more preferably an imidazole-based curing accelerator. The curing accelerator may be used alone or in combination of two or more kinds.
[0076] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0077] As the amine-based curing accelerator, commercially available products may be used, for example, "PN-50", "PN-23", "MY-25" and the like manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0078] Examples of the imidazole-based curing accelerator include 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl- 2-Methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethyl Examples of imidazole compounds include imidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.
[0079] As the imidazole-based curing accelerator, commercially available products may be used, for example, "2P4MZ" and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0080] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.
[0081] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.
[0082] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0083] From the viewpoint of obtaining the desired effects of the present invention, the (C) curing accelerator is preferably at least one selected from an acid anhydride-based epoxy resin curing agent, an amine-based curing accelerator, and an imidazole-based curing accelerator, and more preferably at least one selected from an amine-based curing accelerator and an imidazole-based curing accelerator.
[0084] From the viewpoint of promoting the curing of the magnetic composition, the content of the (C) curing accelerator is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and even more preferably 0.05 mass% or more, based on 100 mass% of the non-volatile components in the magnetic composition, and the upper limit is preferably 0.5 mass% or less, more preferably 0.3 mass% or less, and even more preferably 0.1 mass% or less.
[0085] <(D) Dispersant> The magnetic composition may further contain (D) a dispersant as an optional component.
[0086] (D) Examples of dispersants include phosphate ester-based dispersants such as polyoxyethylene alkyl ether phosphate; anionic dispersants such as sodium dodecyl benzyl sulfonate, sodium laurate, and ammonium salts of polyoxyethylene alkyl ether sulfate; and nonionic dispersants such as organosiloxane-based dispersants, acetylene glycol, polyoxyethylene alkyl ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene alkyl phenyl ether, polyoxyethylene alkyl amine, and polyoxyethylene alkyl amide. Among these, anionic dispersants are preferred. Dispersants may be used alone or in combination of two or more.
[0087] The phosphate ester-based dispersant may be a commercially available product, such as "RS-410," "RS-610," or "RS-710" from the "Phosphanol" series manufactured by Toho Chemical Industry Co., Ltd.
[0088] Examples of commercially available organosiloxane dispersants include "BYK347" and "BYK348" manufactured by BYK-Chemie.
[0089] Commercially available polyoxyalkylene dispersants include "AKM-0531", "AFB-1521", "SC-0505K", "SC-1015F", "SC-0708A", and "HKM-50A" from the "Marialim" series manufactured by NOF Corporation.
[0090] Commercially available acetylene glycols include the "Surfynol" series manufactured by Air Products and Chemicals Inc., such as "82", "104", "440", "465", and "485", as well as "Olefin Y".
[0091] In order to prominently exhibit the effects of the present invention, the content of the dispersant (D) is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, based on 100% by mass of the non-volatile components in the magnetic composition, and the upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.
[0092] <(E) Other Additives> The magnetic composition may further contain (E) other additives as necessary. Examples of such other additives include a cure retarder such as triethyl borate for improving pot life, inorganic fillers (excluding those corresponding to magnetic powders), flame retardants, organic fillers, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds, and resin additives such as thickeners, defoamers, leveling agents, adhesion promoters, and colorants.
[0093] The magnetic composition may be a paste-like composition that exhibits the characteristic of low viscosity even without containing a solvent. Therefore, the content of the solvent contained in the magnetic composition is preferably less than 1.0 mass%, more preferably 0.8 mass% or less, even more preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less, based on the total mass of the magnetic composition. There is no particular limit to the lower limit, but it is 0.001 mass% or more, or no solvent is contained. The magnetic composition can have a low viscosity even without containing a solvent by using a thermosetting resin or the like that is usually in a liquid state. The small amount of solvent in the magnetic composition can suppress the generation of voids due to the evaporation of the solvent, and can also be made excellent in handleability and workability.
[0094] <Method of manufacturing magnetic composition> The magnetic composition can be produced, for example, by a method in which the ingredients are mixed together using a mixing device such as a three-roll mixer or a rotary mixer.
[0095] <Physical properties of magnetic composition> Since the magnetic composition contains component (A) having a predetermined particle size distribution, the cured product of the magnetic composition exhibits the characteristic of high relative magnetic permeability. Therefore, the cured product of the magnetic composition produces a magnetic layer with high relative magnetic permeability. The relative magnetic permeability of this cured product at a frequency of 10 MHz is preferably 15 or more, more preferably 17 or more, and even more preferably 19 or more. The upper limit is not particularly limited, but may be 100 or less. The relative magnetic permeability can be measured according to the method described in the examples below.
[0096] Since the magnetic composition contains component (A) having a predetermined particle size distribution, the cured product of the magnetic composition exhibits the characteristic of low magnetic loss. Therefore, the cured product of the magnetic composition produces a magnetic layer with low magnetic loss. The magnetic loss of this cured product at a frequency of 10 MHz is preferably less than 0.08, more preferably 0.05 or less, and even more preferably 0.04 or less, less than 0.05. The lower limit is not particularly limited, but may be 0.0001 or more. The magnetic loss can be measured according to the method described in the examples below.
[0097] The magnetic composition usually exhibits a characteristic of low viscosity. Therefore, the magnetic composition has a characteristic of being pasty (paste-like magnetic composition), and can be suitably used as a magnetic composition for filling through-holes. In addition, the magnetic composition can be suitably used as a magnetic composition for forming an inductor base element for producing an inductor element.
[0098] [Magnetic sheet] The magnetic sheet includes a support and a magnetic composition layer formed from the magnetic composition of the present invention provided on the support.
[0099] From the viewpoint of thinning, the thickness of the magnetic composition layer is preferably 250 μm or less, more preferably 200 μm or less. The lower limit of the thickness of the magnetic composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.
[0100] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0101] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0102] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0103] The surface of the support which is to be bonded to the magnetic composition layer may be subjected to a matte treatment or a corona treatment.
[0104] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the magnetic composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "PET501010", "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0105] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0106] In the magnetic sheet, a protective film similar to that of the support can be further laminated on the surface of the magnetic composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the magnetic composition layer. The magnetic sheet can be wound up in a roll and stored. When the magnetic sheet has a protective film, it can be used by peeling off the protective film.
[0107] The magnetic sheet can be produced, for example, by applying the magnetic composition to a support using a die coater or the like to form a magnetic composition layer. If necessary, a resin varnish dissolved in an organic solvent may be prepared, and this resin varnish may be applied to the support. When an organic solvent is used, drying may be performed after application if necessary.
[0108] Drying may be performed by heating, blowing hot air, or the like. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the magnetic composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the components contained in the magnetic composition, a magnetic composition layer can be formed by drying at 50°C to 150°C for 3 to 10 minutes.
[0109] The magnetic sheet can be stored in a rolled state. If the magnetic sheet has a protective film, it can be used by peeling off the protective film.
[0110] [Circuit board and its manufacturing method] The circuit board of the present invention includes a magnetic layer that is a cured product of a magnetic composition. The circuit board of the first embodiment includes a substrate having a through hole and a cured product of the magnetic composition of the present invention that fills the through hole. The circuit board of the second embodiment includes a magnetic layer formed by a cured product of a magnetic composition layer of a magnetic sheet. Hereinafter, the first and second embodiments of the method for manufacturing a circuit board will be described. However, the method for manufacturing a circuit board according to the present invention is not limited to the first and second embodiments exemplified below.
[0111] First Embodiment The circuit board of the first embodiment is manufactured, for example, by a manufacturing method including the following steps (1) to (5). In the first embodiment, the magnetic layer is preferably formed using a magnetic composition, and more preferably, the magnetic layer is formed using a paste-like magnetic composition. (1) filling a through-hole of a substrate having a through-hole with a magnetic composition; (2) a step of thermally curing the magnetic composition to obtain a cured product; (3) A step of polishing the surface of the cured product or the magnetic composition (4) roughening the cured product; and (5) forming a conductive layer on the roughened surface of the cured product. The method for producing a circuit board of the present invention may be carried out in the order of steps (1) to (5), or step (2) may be carried out after step (3).
[0112] <Process (1)> The step (1) may include a step of preparing a magnetic composition. The magnetic composition is as described above.
[0113] 1, the process may include a step of preparing a core substrate 10 including a support substrate 11, a first metal layer 12 made of a metal such as copper foil provided on both surfaces of the support substrate 11, and a second metal layer 13. Examples of materials for the support substrate 11 include insulating substrates such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. Examples of materials for the first and second metal layers include copper foil with a carrier, and materials for the conductor layers described later.
[0114] 2, a step of forming through holes 14 in the core substrate 10 may be included. The through holes 14 can be formed by, for example, drilling, laser irradiation, plasma irradiation, etc. Specifically, the through holes 14 can be formed by forming through holes in the core substrate 10 using a drill or the like.
[0115] The through holes 14 can be formed by using a commercially available drilling device. An example of a commercially available drilling device is "ND-1S211" manufactured by Hitachi Via Mechanics.
[0116] After forming through holes 14 in core substrate 10, the process may include a step of roughening core substrate 10 and forming plating layer 20 within through holes 14, on the surface of first metal layer 12, and on the surface of second metal layer 13, as shown in an example in FIG. 3.
[0117] The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order.
[0118] The plating layer 20 is formed by a plating method, and the procedure for forming the plating layer 20 by a plating method is similar to the formation of the conductive layer in step (5) described below.
[0119] After preparing the core substrate 10, the magnetic composition 30a is filled into the through-holes 14, as shown in FIG. 4. The filling can be performed by, for example, a printing method. Examples of the printing method include a method of printing the magnetic composition 30a into the through-holes 14 using a squeegee, a method of printing the magnetic composition 30a using a cartridge, a method of printing the magnetic composition 30a by mask printing, a roll coating method, an inkjet method, and the like.
[0120] <Process (2)> In step (2), the through-hole 14 is filled with the magnetic composition 30a, and the magnetic composition 30a is thermally cured to form a cured layer (magnetic layer) 30 in the through-hole 14, as shown in FIG. 5. The thermal curing conditions of the magnetic composition 30a vary depending on the composition and type of the magnetic composition 30a, but the curing temperature is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and is preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The curing time of the magnetic composition 30a is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and is preferably 120 minutes or lower, more preferably 100 minutes or lower, and even more preferably 90 minutes or lower.
[0121] The degree of hardening of the magnetic layer 30 in step (2) is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The degree of hardening can be measured, for example, using a differential scanning calorimeter.
[0122] Before thermally curing the magnetic composition 30a, the magnetic composition 30a may be subjected to a preheating treatment in which the magnetic composition 30a is heated at a temperature lower than the curing temperature. For example, prior to thermally curing the magnetic composition 30a, the magnetic composition 30a may be preheated at a temperature of usually 50°C or higher and lower than 120°C (preferably 60°C or higher and 110°C or lower, more preferably 70°C or higher and 100°C or lower) for usually 5 minutes or longer (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).
[0123] When step (3) is carried out after step (2), a heat treatment may be carried out after step (2) and before step (3) if necessary, for the purpose of further increasing the degree of hardening of the magnetic layer. The temperature in the heat treatment may be in accordance with the above-mentioned hardening temperature, and is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and is preferably 90 minutes or lower, more preferably 70 minutes or lower, and even more preferably 60 minutes or lower.
[0124] Furthermore, when step (3) is performed before step (2), a preheating treatment may be performed before step (3) by heating at a temperature lower than the curing temperature of the magnetic composition. The temperature in the preheating treatment is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or longer, more preferably 10 minutes or longer, and even more preferably 15 minutes or longer, and preferably 90 minutes or lower, more preferably 70 minutes or lower, and even more preferably 60 minutes or lower.
[0125] <Process (3)> In step (3), as shown in Fig. 6, the excess magnetic layer 30 protruding from or attached to the core substrate 10 is removed by polishing to flatten it. As the polishing method, a method capable of polishing the excess magnetic layer 30 protruding from or attached to the core substrate 10 can be used. Examples of such polishing methods include buff polishing and belt polishing. An example of a commercially available buff polishing device is "NT-700IM" manufactured by Ishii Hyoki Co., Ltd.
[0126] The arithmetic mean roughness (Ra) of the polished surface of the magnetic layer (after the magnetic layer is thermally cured) is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0127] When step (3) is carried out after step (2), a heat treatment may be carried out after step (2) and before step (3) if necessary, for the purpose of further increasing the degree of hardening of the magnetic layer. The temperature in the heat treatment may be in accordance with the above-mentioned hardening temperature, and is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and is preferably 90 minutes or lower, more preferably 70 minutes or lower, and even more preferably 60 minutes or lower.
[0128] Furthermore, when step (3) is performed before step (2), a preheating treatment may be performed before step (3) by heating at a temperature lower than the curing temperature of the magnetic composition. The temperature in the preheating treatment is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or longer, more preferably 10 minutes or longer, and even more preferably 15 minutes or longer, and preferably 90 minutes or lower, more preferably 70 minutes or lower, and even more preferably 60 minutes or lower.
[0129] <Process (4)> In step (4), the surface polished in step (3) is roughened (desmeared). The procedure and conditions of the roughening step are not particularly limited, and known procedures and conditions that are usually used in the manufacturing method of a multilayer printed wiring board can be adopted. As the roughening step, for example, the first magnetic layer 32 can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0130] The swelling liquid that can be used in the roughening step is not particularly limited, but includes an alkaline solution, a surfactant solution, and the like, and is preferably an alkaline solution. As the alkaline solution that is the swelling liquid, a sodium hydroxide solution and a potassium hydroxide solution are more preferable. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan.
[0131] The swelling treatment with the swelling liquid is not particularly limited, but can be carried out, for example, by immersing the core substrate 20 on which the first magnetic layer 32 is provided for 1 to 20 minutes in a swelling liquid at 30° C. to 90° C. From the viewpoint of suppressing swelling of the resin constituting the first magnetic layer 32 to an appropriate level, it is preferable to immerse the first magnetic layer 32 in a swelling liquid at 40° C. to 80° C. for 5 to 15 minutes.
[0132] The oxidizing agent that can be used in the roughening treatment with an oxidizing agent is not particularly limited, and examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment with an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the first magnetic layer 32 in an oxidizing agent solution heated to 60°C to 80°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact P" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0133] The neutralizing solution used in the neutralization treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigans P" manufactured by Atotech Japan. The neutralization treatment using a neutralizing solution can be performed by immersing the treated surface that has been roughened with an oxidizing solution in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method of immersing the first magnetic layer 32 that has been roughened with an oxidizing solution in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferable.
[0134] The arithmetic mean roughness (Ra) of the magnetic layer after roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0135] <Process (5)> In step (5), a conductor layer 40 is formed on the polished surface of the magnetic layer 30 and on the core substrate, as shown in an example in Fig. 7. Furthermore, after forming the conductor layer 40, a pattern conductor layer 41 may be formed by removing parts of the conductor layer 40, the first metal layer 12, the second metal layer 13, and the plating layer 20 by a process such as etching, as shown in an example in Fig. 8. In Fig. 7, the conductor layer 40 is formed on both sides of the core substrate 10, but the conductor layer 40 may be formed on only one side of the core substrate 10.
[0136] The method for forming the conductor layer includes, for example, plating, sputtering, vapor deposition, etc., and among these, plating is preferred. In a preferred embodiment, the surface of the cured product is plated by an appropriate method such as a semi-additive method or a full additive method to form a patterned conductor layer having a desired wiring pattern. Examples of the material for the conductor layer include single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium; and alloys of two or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among these, from the viewpoints of versatility, cost, ease of patterning, etc., it is preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy, and it is more preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, and it is even more preferable to use copper.
[0137] Here, an example of an embodiment in which a patterned conductor layer is formed on the polished surface of the cured product will be described in detail. A plating seed layer is formed on the polished surface of the cured product by electroless plating. Then, an electrolytic plating layer is formed on the formed plating seed layer by electrolytic plating, and unnecessary plating seed layer is removed by etching or other treatment as necessary to form a conductor layer having a desired wiring pattern. After the conductor layer is formed, an annealing treatment may be performed as necessary for the purpose of improving the peel strength of the conductor layer. The annealing treatment can be performed, for example, by heating the circuit board at 150 to 200°C for 20 to 90 minutes.
[0138] From the viewpoint of thinning, the thickness of the patterned conductor layer is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0139] <Second embodiment> The circuit board of the second embodiment includes a magnetic layer formed by a cured product of the magnetic composition. In the second embodiment, it is preferable to form the magnetic layer using a magnetic sheet. Hereinafter, the second embodiment of the method for manufacturing the product board will be described. Explanations of parts that overlap with the first embodiment will be omitted as appropriate.
[0140] The circuit board of the second embodiment is manufactured, for example, by a manufacturing method including the following steps (A) to (D). (A) a step of laminating a magnetic sheet onto an inner layer substrate such that the magnetic composition layer is bonded to the inner layer substrate to form a magnetic layer; (B) a step of drilling holes in the magnetic layer; (C) a step of roughening the surface of the magnetic layer; and (D) forming a conductive layer on the polished surface of the magnetic layer.
[0141] The above steps (A) to (D) for manufacturing the circuit board will now be described in detail.
[0142] <Process (A)> Step (A) is a step of laminating a magnetic sheet on an inner layer substrate such that the magnetic composition layer is bonded to the inner layer substrate to form a magnetic layer. In one embodiment of step (A), the magnetic sheet is laminated on the inner layer substrate such that the magnetic composition layer is bonded to the inner layer substrate, and the magnetic composition layer is thermally cured to form the magnetic layer.
[0143] In step (A), as shown in an example in Figure 9, a magnetic sheet 310 including a support 330 and a magnetic composition layer 320a provided on the support 330 is laminated onto an inner layer substrate 200 so that the magnetic composition layer 320a is bonded to the inner layer substrate 200.
[0144] The inner layer substrate 200 is an insulating substrate. Examples of materials for the inner layer substrate 200 include insulating base materials such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The inner layer substrate 200 may be an inner layer circuit substrate having wiring and the like built into its thickness.
[0145] As shown in Fig. 9 as an example, the inner layer substrate 200 has a first conductor layer 420 provided on the first main surface 200a and an external terminal 240 provided on the second main surface 200b. The first conductor layer 420 may include a plurality of wirings. In the illustrated example, only the wirings constituting the coil-shaped conductive structure 400 of the inductor element are shown. The external terminal 240 is a terminal for electrically connecting to an external device or the like (not shown). The external terminal 240 can be configured as a part of the conductor layer provided on the second main surface 200b.
[0146] The conductive material that can form the first conductive layer 420 and the external terminals 240 is similar to the material of the conductive layer explained in the section “<Step (5)>” of the first embodiment.
[0147] The first conductor layer 420 and the external terminal 240 may have a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different types of metals or alloys are laminated. The thickness of the first conductor layer 420 and the external terminal 240 is the same as that of the second conductor layer 440 described later.
[0148] The line (L) / space (S) ratio of the first conductor layer 420 and the external terminal 240 is not particularly limited, but from the viewpoint of obtaining a magnetic layer with excellent smoothness by reducing surface irregularities, it is usually 900 / 900 μm or less, preferably 700 / 700 μm or less, more preferably 500 / 500 μm or less, even more preferably 300 / 300 μm or less, and even more preferably 200 / 200 μm or less. The lower limit of the line / space ratio is not particularly limited, but from the viewpoint of improving the embedding of the magnetic composition layer in the space, it is preferably 1 / 1 μm or more.
[0149] The inner layer substrate 200 may have a plurality of through holes 220 penetrating the inner layer substrate 200 from the first main surface 200a to the second main surface 200b. The through holes 220 are provided with through hole wiring 220a. The through hole wiring 220a electrically connects the first conductor layer 420 and the external terminal 240.
[0150] The magnetic composition layer 320a and the inner layer substrate 200 can be bonded, for example, by thermocompression bonding the magnetic sheet 310 to the inner layer substrate 200 from the support 330 side. Examples of a member for thermocompression bonding the magnetic sheet 310 to the inner layer substrate 200 (hereinafter also referred to as a "thermocompression bonding member") include a heated metal plate (such as a stainless steel (SUS) plate) or a metal roll (SUS roll). Note that, rather than pressing the magnetic sheet 310 by directly contacting it with the thermocompression bonding member, it is preferable to press the magnetic sheet 310 via a sheet made of an elastic material such as heat-resistant rubber so that the magnetic sheet 310 can sufficiently follow the irregularities on the surface of the inner layer substrate 200.
[0151] The temperature during thermocompression bonding is preferably in the range of 80°C to 160°C, more preferably 90°C to 140°C, and even more preferably 100°C to 120°C, the pressure during thermocompression bonding is preferably in the range of 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the time during thermocompression bonding is preferably in the range of 20 seconds to 400 seconds, and more preferably 30 seconds to 300 seconds. The bonding of the magnetic sheet and the inner layer substrate is preferably carried out under reduced pressure conditions of 26.7hPa or less.
[0152] The magnetic composition layer 320a of the magnetic sheet 310 can be bonded to the inner layer substrate 200 by a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd. and a vacuum applicator manufactured by Nikko Materials Co., Ltd.
[0153] After bonding the magnetic sheet 310 and the inner layer substrate 200, the laminated magnetic sheet 310 may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing process may be the same as the thermocompression conditions for the lamination. The smoothing process may be performed using a commercially available laminator. Note that the lamination and the smoothing process may be performed consecutively using the commercially available vacuum laminator.
[0154] After the magnetic sheet is laminated on the inner layer substrate, the magnetic composition layer is thermally cured to form a magnetic layer. As shown in FIG. 10, the magnetic composition layer 320a bonded to the inner layer substrate 200 is thermally cured to form the first magnetic layer 320.
[0155] The thermal curing conditions of the magnetic composition layer 320a vary depending on the composition and type of the magnetic composition, but the curing temperature is preferably 120° C. or more, more preferably 130° C. or more, even more preferably 150° C. or more, and preferably 245° C. or less, more preferably 220° C. or less, and even more preferably 200° C. or less. The curing time of the magnetic composition layer 320a is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and preferably 120 minutes or less, more preferably 100 minutes or less, and even more preferably 90 minutes or less.
[0156] The support 330 may be removed between the end of the thermal curing in step (A) and step (B), or may be peeled off after step (B).
[0157] The arithmetic mean roughness (Ra) of the magnetic layer before roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with plating. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0158] In step (A), instead of using a magnetic sheet, a magnetic composition may be applied onto the inner layer substrate using a die coater or the like, and then thermally cured to form a magnetic layer.
[0159] <Process (B)> In step (B), as shown in FIG. 11, the first magnetic layer 320 is drilled to form a via hole 360. The via hole 360 serves as a path for electrically connecting the first conductor layer 420 and a second conductor layer 440 described below. The via hole 360 may be formed using, for example, a drill, a laser, plasma, or the like, depending on the composition of the magnetic composition used to form the magnetic layer. The size and shape of the hole may be appropriately determined depending on the design of the printed wiring board.
[0160] <Process (C)> In step (C), the surface of the magnetic layer in which the via holes are formed is roughened as described in the section “<Step (4)>” of the first embodiment.
[0161] The arithmetic mean roughness (Ra) of the magnetic layer after roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0162] In step (C), polishing may be performed instead of the roughening treatment to remove and flatten the excess magnetic layer protruding from or adhering to the core substrate 10. The polishing method is as described above.
[0163] <Process (D)> In step (D), a second conductor layer 440 is formed on the first magnetic layer 320, as shown in an example in FIG.
[0164] The conductive material that can form the second conductive layer 440 is similar to the material of the conductive layer explained in the section “<Step (5)>” of the first embodiment.
[0165] From the viewpoint of thinning, the thickness of the second conductor layer 440 is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0166] The second conductor layer 440 can be formed by plating. The second conductor layer 440 is preferably formed by a wet plating method such as a semi-additive method or a full-additive method including an electroless plating process, a mask pattern forming process, an electrolytic plating process, and a flash etching process. By forming the second conductor layer 440 using a wet plating method, it is possible to form the second conductor layer 440 including a desired wiring pattern. Note that this process also forms an in-via-hole wiring 360a in the via hole 360.
[0167] The first conductor layer 420 and the second conductor layer 440 may be provided in a spiral shape, for example, as shown in Figs. 13 to 15 described later. In one example, one end of the spiral wiring part of the second conductor layer 440 on the center side is electrically connected to one end of the spiral wiring part of the first conductor layer 420 on the center side by the via-hole wiring 360a. The other end of the spiral wiring part of the second conductor layer 440 on the outer periphery side is electrically connected to the land 420a of the first conductor layer 42 by the via-hole wiring 360a. Therefore, the other end of the spiral wiring part of the second conductor layer 440 on the outer periphery side is electrically connected to the external terminal 240 via the via-hole wiring 360a, the land 420a, and the through-hole wiring 220a.
[0168] The coil-shaped conductive structure 400 is composed of a spiral wiring portion that is a part of the first conductor layer 420, a spiral wiring portion that is a part of the second conductor layer 440, and via-hole wiring 360a that electrically connects the spiral wiring portion of the first conductor layer 420 and the spiral wiring portion of the second conductor layer 440.
[0169] After step (D), a step of forming a magnetic layer on the conductor layer may be performed. In detail, as shown in an example in Fig. 14, a second magnetic layer 340 is formed on the first magnetic layer 320 on which the second conductor layer 440 and the via-hole wiring 360a are formed. The second magnetic layer may be formed by the same steps as those already described.
[0170] [Inductor board] The inductor substrate includes the circuit substrate of the present invention. When such an inductor substrate includes a circuit substrate obtained by the method for producing a circuit substrate according to the first embodiment, the inductor substrate has an inductor pattern formed by a conductor at least in a part of the periphery of the cured product of the magnetic composition. For example, the inductor substrate described in JP 2016-197624 A can be used.
[0171] Furthermore, when the inductor substrate includes a circuit board obtained by the circuit board manufacturing method of the second embodiment, the inductor substrate has a magnetic layer and a conductive structure at least partially embedded in the magnetic layer, and includes an inductor element formed by the conductive structure and a part of the magnetic layer that extends in the thickness direction of the magnetic layer and is surrounded by the conductive structure. Here, Fig. 13 is a schematic plan view of the inductor substrate having the inductor element as viewed from one side in the thickness direction. Fig. 14 is a schematic view showing a cut end surface of the inductor substrate cut at the position indicated by the dashed line II-II in Fig. 13. Fig. 15 is a schematic plan view for explaining the configuration of a first conductive layer of the inductor substrate.
[0172] 13 and 14, the circuit board 100 is a build-up wiring board having a plurality of magnetic layers (first magnetic layer 320, second magnetic layer 340) and a plurality of conductor layers (first conductor layer 420, second conductor layer 440), i.e., a build-up magnetic layer and a build-up conductor layer. The inductor board 100 also includes an inner layer board 200.
[0173] 14, the first magnetic layer 320 and the second magnetic layer 340 constitute the magnetic part 300 which can be seen as an integrated magnetic layer. Therefore, the coiled conductive structure 400 is provided so that at least a portion thereof is embedded in the magnetic part 300. That is, in the inductor substrate 100 of this embodiment, the inductor element is constituted by the coiled conductive structure 400 and a core portion which is a portion of the magnetic part 300 that extends in the thickness direction of the magnetic part 300 and is surrounded by the coiled conductive structure 400.
[0174] 15, the first conductor layer 420 includes a spiral wiring portion for constituting the coil-shaped conductive structure 400, and a rectangular land 420a electrically connected to the through-hole wiring 220a. In the illustrated example, the spiral wiring portion includes a straight portion and a bent portion that is bent at a right angle, and a detour portion that detours around the land 420a. In the illustrated example, the spiral wiring portion of the first conductor layer 420 has an overall outline that is approximately rectangular, and has a shape that winds counterclockwise from the center toward the outside.
[0175] Similarly, a second conductor layer 440 is provided on the first magnetic layer 320. The second conductor layer 440 includes a spiral wiring portion for configuring the coil-shaped conductive structure 400. In Fig. 13 or 14, the spiral wiring portion includes a straight portion and a bent portion bent at a right angle. In Fig. 13 or 14, the spiral wiring portion of the second conductor layer 44 has an overall outline that is substantially rectangular, and has a shape that is wound clockwise from the center toward the outside.
[0176] Such an inductor substrate can be used as a wiring board for mounting electronic components such as semiconductor chips, and can also be used as a (multilayer) printed wiring board using such a wiring board as an inner layer substrate.Furthermore, such a wiring board can be used as an individual chip inductor component, and can also be used as a printed wiring board with the chip inductor component surface mounted.
[0177] In addition, various types of semiconductor devices can be manufactured using such a wiring board. The semiconductor device including such a wiring board can be suitably used in electric products (e.g., computers, mobile phones, digital cameras, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES
[0178] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the terms "parts" and "%" used to express amounts refer to "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0179] <Example 1: Preparation of magnetic composition 1> Epoxy resin a ("ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.) 15 parts by mass, epoxy resin b ("ZX-1658GS", liquid 1,4-glycidylcyclohexane, manufactured by Nippon Steel Chemical & Material Co., Ltd.) 5 parts by mass, curing accelerator a ("2MZA-PW", an imidazole curing accelerator, manufactured by Shikoku Kasei Co., Ltd.) 1 part by mass, magnetic powder a (Fe-based nanocrystalline magnetic material, "KUAMET NC1", manufactured by Epson Atomics Corporation, D 50 : 25 μm) 40 parts by mass, magnetic powder c (Epson Atmix, Fe-based nanocrystalline magnetic material, "ATFINE NC1", D 50 3 μm) were mixed to prepare magnetic composition 1.
[0180] <Example 2: Preparation of magnetic composition 2> In Example 1, magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, "KUAMET NC1", D 50 40 parts by mass of magnetic powder b (manufactured by Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) 40 parts by weight, Magnetic powder c (Epson Atmix, Fe-based nanocrystalline magnetic material, "ATFINE NC1"), D 50 60 parts by mass of magnetic powder d (manufactured by Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F", D 50 :3 μm) was changed to 60 parts by mass. Magnetic composition 2 was prepared in the same manner as in Example 1 except for the above.
[0181] <Example 3: Preparation of magnetic composition 3> In Example 1, magnetic powder c (manufactured by Epson Atmix, Fe-based nanocrystalline magnetic material, "ATFINE NC1", D 50 60 parts by mass of magnetic powder d (manufactured by Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F", D 50 :3μm) 60 parts. Magnetic composition 3 was prepared in the same manner as in Example 1 except for the above.
[0182] <Example 4: Preparation of magnetic composition 4> In Example 1, magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, "KUAMET NC1", D 50 40 parts by mass of magnetic powder b (manufactured by Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) was changed to 40 parts by mass. Magnetic composition 4 was prepared in the same manner as in Example 1 except for the above.
[0183] <Example 5: Preparation of magnetic composition 5> Epoxy resin a ("ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.) 1.5 parts by mass, epoxy resin b ("ZX-1658GS", liquid 1,4-glycidylcyclohexane, manufactured by Nippon Steel Chemical & Material Co., Ltd.) 0.5 parts by mass, curing accelerator a ("2MZA-PW", an imidazole curing accelerator, manufactured by Shikoku Kasei Co., Ltd.) 0.1 parts by mass, magnetic powder b (Fe-based amorphous magnetic material, "KUAMET 6B2", manufactured by Epson Atomics Corporation, D 50 25 μm) 30 parts by mass, magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F", D 50 70 parts by mass of ferromagnetic powder (0.3 μm) were mixed together to prepare magnetic composition 5.
[0184] <Example 6: Preparation of magnetic composition 6> In Example 5, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D50 : 25 μm) from 30 parts by weight to 25 parts by weight, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 The amount of the cellulose acylate (: 3 μm) was changed from 70 parts by mass to 75 parts by mass. Magnetic composition 6 was prepared in the same manner as in Example 5 except for the above.
[0185] <Example 7: Preparation of magnetic composition 7> In Example 5, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) from 30 parts by mass to 40 parts by mass, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 The amount of the cellulose acylate (: 3 μm) was changed from 70 parts by mass to 60 parts by mass. Magnetic composition 7 was prepared in the same manner as in Example 5 except for the above.
[0186] <Example 8: Preparation of magnetic composition 8> In Example 5, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 25 μm) from 30 parts by weight to 50 parts by weight, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 The amount of the cellulose acylate (: 3 μm) was changed from 70 parts by mass to 50 parts by mass. Magnetic composition 8 was prepared in the same manner as in Example 5 except for the above.
[0187] <Example 9: Preparation of Magnetic Composition 9> In Example 5, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) from 30 parts by mass to 80 parts by mass, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 3 μm) 70 parts by mass of magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, “KUAMET NC1”, D 50 : 25 μm) was changed to 20 parts by mass. Magnetic composition 9 was prepared in the same manner as in Example 5 except for the above.
[0188] Example 10: Preparation of magnetic composition 10 In Example 5, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) from 30 parts by mass to 45 parts by mass, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 3 μm) 70 parts by mass of magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, “KUAMET NC1”, D 50 : 25 μm) was changed to 55 parts by mass. A magnetic composition 10 was prepared in the same manner as in Example 5 except for the above.
[0189] <Comparative Example 1: Preparation of Magnetic Composition 11> In Example 1, magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, "KUAMET NC1", D 50 : 25 μm) from 40 parts by mass to 100 parts by mass, Magnetic powder c (Epson Atmix, Fe-based nanocrystalline magnetic material, "ATFINE NC1"), D 50 :3 μm) 60 parts by mass was not used. Magnetic composition 11 was prepared in the same manner as in Example 1 except for the above points.
[0190] <Comparative Example 2: Preparation of Magnetic Composition 12> In Example 1, magnetic powder c (manufactured by Epson Atmix, Fe-based nanocrystalline magnetic material, "ATFINE NC1", D 503μm) from 60 parts by mass to 100 parts by mass, Magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, "KUAMET NC1"), D 50 :25 μm) 40 mass was not used. A magnetic composition 12 was prepared in the same manner as in Example 1 except for the above points.
[0191] <Comparative Example 3: Preparation of Magnetic Composition 13> In Example 2, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) from 40 parts by mass to 100 parts by mass, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 :3 μm) 60 parts were not used. A magnetic composition 13 was prepared in the same manner as in Example 2 except for the above.
[0192] <Comparative Example 4: Preparation of Magnetic Composition 14> In Example 2, magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F", D 50 3μm) from 60 parts by weight to 100 parts by weight, Magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) 40 parts by mass was not used. A magnetic composition 14 was prepared in the same manner as in Example 2 except for the above.
[0193] Comparative Example 5: Preparation of Magnetic Composition 15 In Example 2, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) from 40 parts by mass to 60 parts by mass, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50The amount of the cellulose acylate (3 μm) was changed from 60 parts by weight to 40 parts by weight. Magnetic composition 15 was prepared in the same manner as in Example 2 except for the above.
[0194] <Comparative Example 6: Preparation of Magnetic Composition 16> In Example 1, magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, "KUAMET NC1", D 50 : 25 μm) from 40 parts by mass to 60 parts by mass, Magnetic powder c (Epson Atmix, Fe-based nanocrystalline magnetic material, "ATFINE NC1"), D 50 The amount of the cellulose acylate (: 3 μm) was changed from 60 parts by mass to 40 parts by mass. A magnetic composition 16 was prepared in the same manner as in Example 1 except for the above points.
[0195] <Comparative Example 7: Preparation of Magnetic Composition 17> In Example 5, magnetic powder b (Epson Atmix, Fe-based amorphous magnetic material, "KUAMET 6B2", D 50 : 25 μm) from 30 parts by mass to 40 parts by mass, Magnetic powder d (Epson Atmix, Fe-based amorphous magnetic material, "AW02-08PF3F"), D 50 3 μm) 70 parts by mass of magnetic powder a (Epson Atmix, Fe-based nanocrystalline magnetic material, “KUAMET NC1”, D 50 : 25 μm) was changed to 60 parts by mass. Magnetic composition 17 was prepared in the same manner as in Example 5 except for the above.
[0196] <Measurement of particle size distribution of component (A)> The magnetic powder was dispersed in pure water by ultrasonic waves to prepare a measurement sample. The measurement sample was measured using a laser diffraction scattering type particle size distribution measurement device ("MT3000II" manufactured by Microtrackbell Co., Ltd.) to measure the D 10 , D 50 , and D 90 was measured.
[0197] <Measurement of relative permeability and magnetic loss> As a support, a polyethylene terephthalate (PET) film ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) treated with a silicone-based release agent was prepared. Each of the magnetic compositions 1 to 17 was uniformly applied to the release surface of the PET film with a doctor blade so that the thickness of the magnetic composition layer after drying was 100 μm, to obtain a magnetic sheet. The magnetic sheet obtained was heated at 190° C. for 90 minutes to thermally cure the magnetic composition layer, and the support was peeled off to obtain a sheet-like cured product. The obtained cured product was cut into a test piece with a width of 5 mm and a length of 18 mm to be used as an evaluation sample. The evaluation sample was measured for relative permeability (μ') and its imaginary component (μ'') at room temperature of 23° C. using an Agilent Technologies ("HP8362B" manufactured by Agilent Technologies) at a measurement frequency of 10 MHz by a 3-turn coil method, and the magnetic loss was calculated from μ'' / μ'.
[0198] The relative permeability was evaluated according to the following criteria. ○: Relative permeability is 17 or more △: Relative permeability is 15 or more and less than 17 ×: Relative permeability is less than 15
[0199] The magnetic loss was evaluated according to the following criteria. 〇: Magnetic loss is less than 0.05 △: Magnetic loss is 0.05 or more and less than 0.08 ×: Magnetic loss is 0.08 or more
[0200] [Table 1] [Table 2]
[0201] (A) Component D 10 , D 50 , and D 90 It can be seen that, compared with Comparative Examples 1 to 7, Examples 1 to 10, in which R is within the predetermined range, are superior in relative permeability and have reduced magnetic loss. [Explanation of symbols]
[0202] 10 Core Board 11 Support substrate 12 1st metal layer 13 Second metal layer 14 through hole 20 Plating layer 30a magnetic composition 30 Magnetic layer 40 Conductor Layer 41 Patterned conductor layer 100 Circuit Board 200 Inner layer board 200a 1st main surface 200b 2nd main surface 220 through hole 220a Through hole wiring 240 External terminal 300 Magnetic part 310 Magnetic Sheet 320a magnetic composition layer 320 First insulating layer 330 Support 340 Second insulating layer 360 Beer Hall 360a via hole wiring 400 Coil-shaped conductive structure 420 First conductor layer 420a Land 440 Second conductor layer
Claims
1. (A) a magnetic powder, and (B) a binder resin, (A) 10% particle size in the particle size distribution of the component (D 10 ) is 1.7 μm or more and 2.6 μm or less, 50% particle size (D 50 ) is 3.6 μm or more and 6.0 μm or less, and the 90% particle size (D 90 ) is 25.0 μm or more and 51.0 μm or less, The component (B) contains a liquid epoxy resin, The liquid epoxy resin is present in an amount of 1% by mass or more and 30% by mass or less relative to 100% by mass of the component (A), The component (A) contains two or more types of magnetic powders having different average particle sizes, and when the average particle size of one magnetic powder is a1 and the average particle size of the other magnetic powder is a2, a1 / a2 is 5 or more and 8 or less, A paste-like magnetic composition in which component (A) is a soft magnetic powder; provided that a1>a2.
2. 2. The magnetic composition according to claim 1, wherein component (A) is either a nanocrystalline magnetic material or an amorphous magnetic material.
3. 3. The magnetic composition according to claim 1, wherein the component (A) comprises an iron alloy metal powder.
4. 4. The magnetic composition according to claim 1, wherein the component (A) is either an Fe-based nanocrystalline magnetic material or an Fe-based amorphous magnetic material.
5. The magnetic composition according to any one of claims 1 to 4, which is used for forming an inductor element.
6. The magnetic composition according to any one of claims 1 to 5, which is for filling through-holes.
7. A magnetic sheet for forming a magnetic layer by thermally curing a magnetic composition layer, the magnetic sheet comprising: a support; and a magnetic composition layer formed of a magnetic composition and provided on the support, the magnetic composition layer comprising: The magnetic composition comprises: (A) a magnetic powder, and (B) a binder resin, The component (B) contains a thermosetting resin, (A) 10% particle size in the particle size distribution of the component (D 10 ) is 1.7 μm or more and 2.6 μm or less, 50% particle size (D 50 ) is 3.6 μm or more and 6.0 μm or less, and the 90% particle size (D 90 ) is 25.0 μm or more and 51.0 μm or less, The component (B) contains a liquid epoxy resin, The component (A) contains two or more types of magnetic powders having different average particle sizes, and when the average particle size of one magnetic powder is a1 and the average particle size of the other magnetic powder is a2, a1 / a2 is 5 or more and 8 or less, The liquid epoxy resin is 1% by mass or more and 30% by mass or less relative to 100% by mass of the component (A); provided that a1>a2.
8. The magnetic sheet according to claim 7 , wherein the component (B) further comprises a thermoplastic resin.
9. A circuit board comprising a magnetic layer which is a cured product of the magnetic composition according to any one of claims 1 to 6.
10. A circuit board comprising: a substrate having a through-hole; and a cured product of the magnetic composition according to any one of claims 1 to 6, the cured product filling the through-hole.
11. An inductor substrate comprising the circuit board according to claim 9 or 10.
Citation Information
Patent Citations
Reactor, and power conditioner apparatus
JP2009071248A
Silica coating forming method of soft magnetic powder for dust core, and manufacturing method of dust core
JP2009231481A
Soft magnetic material manufacturing member, soft magnetic material, copper-clad laminated plate, print wiring plate, and inductor
JP2013212642A
Metal magnetic powder-containing sheet, method for manufacturing inductor, and inductor
JP2017123433A
Soft magnetic material, core and inductor
JP2018113436A
